COMPARISON OF DIFFERENT DOSES OF INTRATHECAL CLONIDINE AS AN ADJUVANT TO LEVOBUPIVACAINE IN PATIENTS UNDERGOING LOWER LIMB ORTHOPAEDIC SURGERY: A RANDOMIZED DOUBLE-BLIND STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Intrathecal adjuvants are commonly used to improve the quality and duration of spinal anesthesia in lower limb orthopedic surgeries. Clonidine, an α2-adrenergic agonist, prolongs sensory and motor blockade and postoperative analgesia when combined with local anesthetics; however, the optimal intrathecal dose of clonidine with hyperbaric levobupivacaine remains uncertain. Objectives:To evaluate and compare the effects of intrathecal clonidine (15 µg and 30 µg) as an adjuvant to 0.5% hyperbaric levobupivacaine in patients undergoing lower limb orthopedic surgeries. Methods:This prospective, randomized, double-blind study included 99 ASA I–II patients undergoing elective lower limb orthopedic surgery under spinal anesthesia. Patients were randomly allocated into three groups (n=33 each): Group A received hyperbaric levobupivacaine with saline, Group B received levobupivacaine with clonidine 15 µg, and Group C received levobupivacaine with clonidine 30 µg. Sensory and motor block characteristics, duration of postoperative analgesia, hemodynamic parameters, postoperative Visual Analog Scale (VAS) scores, and adverse effects were evaluated and compared among the groups. Results: The onset of sensory and motor blockade was significantly faster in the clonidine groups, particularly in Group C (P < 0.001). Time to attain maximum sensory and motor blockade was also significantly reduced in Group C. Duration of motor block and postoperative analgesia increased with increasing clonidine dose. Mean duration of analgesia was highest in Group C (360.76 ± 55.21 min), followed by Group B (300.68 ± 43.20 min) and Group A (255.80 ± 33.61 min) (P < 0.001). Postoperative VAS scores at 4 hours were significantly lower in Group C. Although intraoperative heart rate and blood pressure were lower in the clonidine groups, the changes remained clinically manageable. Conclusion: Intrathecal clonidine with hyperbaric levobupivacaine improved block characteristics and prolonged postoperative analgesia in a dosedependent manner. Clonidine 30 µg provided longest analgesia but caused greater, clinically manageable hemodynamic effects.